Development of a Cell-Based Assay for Measuring Base Excision Repair Responses. Issue 1 (December 2017) - Golato, Tyler; Brenerman, Boris; McNeill, Daniel; Li, Jianfeng; Sobol, Robert; Wilson, David
Abstract Base excision repair (BER) is the predominant pathway for coping with most forms of hydrolytic, oxidative or alkylative DNA damage. Measuring BER capacity in living cells is valuable for both basic science applications and epidemiological studies, since deficiencies in this pathway have been associated with cancer susceptibility and other adverse health outcomes. At present, there is an ongoing effort to develop methods to effectively quantify the rate of BER as a whole. We present a variation of a previously described "Oligonucleotide Retrieval Assay" designed to measure DNA excision repair that is capable of quantifying the rate of repair of thymine glycol in a variety of human cells with a high degree of sensitivity.